Studying the mechanical properties of (Cu₁₋ₓAgₓ)₇GeS₅I mixed crystals by using the micro-indentation method - Bilanych, V.V.; Bendak, A.V.; Skubenych, K.V.; Pogodin, A.I.; Bilanych, V.S.; Studenyak, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
(Cu₁₋ₓAgₓ)₇GeS₅I mixed crystals were grown using the Bridgman–Stockbarger method. The hardness dependence on the indentation depth profiles in (Cu₁₋ₓAgₓ)₇GeS₅I mixed crystals was investigated. The measurements of mechanical parameters were performed at room temperature by using the micro-indentation method. Variations of the hardness of (Cu₁₋ₓAgₓ)₇GeS₅I mixed crystals were interpreted in the framework of the deformation gradient model. The influence of cation Cu→Ag substitution on the mechanical parameters of (Cu₁₋ₓAgₓ)₇GeS₅I mixed crystals was studied.